The Effect of Contact Lens–spectacle Reversed Galilean Telescope on the Visual Field of Patients with Open-angle Glaucoma - Moniritilaki, Mohammadreza; Badakhsh, Maryam; Ehsaei, Asieh; Daneshvar, Ramin (Journal of Ophthalmic and Vision Research, 2020)
Purpose: Glaucoma causes irreversible visual field defects. This study aims to evaluate the effect of a reversed Galilean telescope on the visual field of patients with open-angle glaucoma. Methods: Fifty-two glaucoma patients with a restricted visual field were recruited for this study. Central 30° visual field measurements were performed using a Humphrey visual field analyzer before and after applying the reversed Galilean telescope. To be more cosmetically acceptable, a combination of contact lens–spectacle was used as the reversed Galilean telescope. Results: Our data analysis showed that the reversed Galilean telescope had a significant effect on all measured perimetric indices. Visual field index (VFI) improved from a basic value of 44.38 ± 26.96 percent to 49.30 ± 29.83 percent by using the reversed telescope (P < 0.001). Moreover, the mean deviation (MD) was significantly improved from the initial value of –19.91 ± 7.19 dB to a value of –18.69 ± 7.73 dB (P < 0.001). However, our results showed a significant reduction in the pattern standard deviation (PSD) comparing before (9.83 ± 2.82) and after (8.51 ± 3.30) values using the reversed Galilean telescope (P < 0.001). Conclusion: The contact lens–spectacle combination reversed Galilean telescope significantly improved the central 30° visual field of glaucoma patients with the restricted visual field.